Some features of proverbs of work “DiwaniLugat at-Turk” (Journal of Oriental Studies, 2017)
Studying and researching the history of language is interesting andchallenging in one breath. You can find those words in today’s Turkish dictionary. In particular, archaic words by changing with due time, withthe change of generations, developing depending on language internal opportunities, in order to ensure its needs, to complete word stock as a result of external influence to develop and change, language are borrowed andmastered words. The article deals with some features of the proverbs in the work of MahmudKashgari “DiwaniLugat at-Turk”, and becomes noticeableeven equivalents that native words, used at the present time.